Comparative of field study of three- and four-bladed archimedes spiral wind turbines under natural low wind conditions - Anas Faroja; Fatahul Arifin; Carlos RS (Jurnal Polimesin, 2026)
Archimedes Spiral Wind Turbines (ASWTs) are suitable for small-scale energy harvesting in low wind environments.However, field-based evaluation on the effect of blade number under natural wind conditions remains limited. This study experimentally examines the influence of blade number on rotational behavior and electrical performance under natural wind conditions, providing empirical insights beyond controlled laboratory and numerical studies. Three-bladed and four-bladed turbine configurations were fabricated and tested in field conditions with wind speeds ranging from 0.8 to 4.0 m/s. Wind speed, rotational speed, voltage, current, and electrical power were measured and analyzed.  The results show that the four-bladed turbine achieved earlier cut-in behavior and consistently higher electrical output across the tested range, reaching a peak power of approximately 0.29 W at wind speeds of 4.0 m/s, compared with about 0.09 W for the three-bladed configuration. The improved performance was attributed to enhanced torque continuity and rotational stability rather than increased rotational speed alone. Transient current peaks and zero-current events observed near 1.5 to 2.0 m/s were attributed near-cut in electromechanical behavior under short-term wind fluctuations. These results confirm that blade number significantly affects ASWT performance in low wind environments and provide practical guidance for optimizing small-scale wind turbine design.